Advances in Nanocatalysis Research for Carbon Nanotubes Formation and Photocatalytic Degradation of Phenol - Abdul Rahman Mohamed; Minoo Tasbihi; Siang-Piao Chai (Bulletin of Chemical Reaction Engineering & Catalysis, 2007)
Catalysis can play two principal roles in nanoscience, including (1) catalysts can be involved in some methods for preparing nanomaterials such as nanotubes; (2) some nanostructures themselves can serve as catalysts for additional chemical reactions. Both nanocatalysis aspects are highlighted in this paper, covering the topics of the use of nanocatalyst for photocatalytic degradation of phenol and methane decomposition into carbon nanotubes (CNTs). © 2007 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)